Omnichannel Marketing and Customer Satisfaction: The Mediating Role of Service Quality Among Generation Z Consumers at Guardian Pekanbaru - Ghina Soraya; Prima Andreas; Dian Pratiwi; Henni Noviasari (West Science Interdisciplinary Studies, 2026)
This study aims to empirically examine the role of omnichannel marketing in enhancing customer satisfaction, with service quality acting as a mediating variable among Generation Z consumers at Guardian Pekanbaru. The integration of marketing channels has become increasingly critical in contemporary consumer behavior, particularly for digitally oriented Generation Z consumers who expect seamless shopping experiences. Data were collected from 100 respondents using a purposive sampling technique, focusing on consumers who had engaged in purchases across multiple channels (online and offline). The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4. The results indicate that omnichannel marketing has a positive and significant effect on both service quality and customer satisfaction. Furthermore, service quality significantly mediates the relationship between omnichannel marketing and customer satisfaction, suggesting that effective channel integration enhances perceived service quality and strengthens customer satisfaction.